Spectral dye Absorbance Interactions of o-Chloroarylimino Crotono o-Chloro Aryl Imino Cadmium Anilide with its Components - N. Modi, Ashvin; Desai, C.M.; Patel, Dinesh (Asian Journal of Chemistry, 2010)
Dye absorbance interactions of o-chloroarylimino-crotono-o-aryliminoanilide and its components, viz, o-chloroaniline, methylacetoacetate, o-chloroarylimino-crotonate have been examined withrespect to cadmium chloride.